Understanding the Resurgence of Coups in West Africa: The Tragedy of the Democracy Project: CODESRIA Bulletin Online, No. 13, December 2025 - Yusuf Bangura, (CODESRIA Bulletin, 2025)
On 26 November 2025, soldiers took over the reins of power in Guinea Bissau, stopped the announcement of the results of the presidential election held three days earlier, which the two contending parties claimed favoured them, and dissolved all political institutions. The soldiers announced that they had done this to save the nation from a plan by politicians and other figures, including a drug lord, to destabilise the country by manipulating the election results. Since 1963, when the African military first struck in Togo and toppled the first president, Sylvanus Olympio, claims of maintaining order and preventing electoral fraud have been among the generic excuses used by soldiers to justify their usurpation of power. The coup in Guinea Bissau is the fifth that the West African region has witnessed since 2020. Mali started the trend in August 2020, when soldiers mutinied against senior military officers and forced an unpopular president, Ibrahim Keïta, to resign. The coup leader, Asimi Goïta, entered into a power-sharing arrangement with a civilian president, Bah Ndaw, with Goïta serving as vice president. However, in May 2021, Goïta overthrew Ndaw and took full control of the government. He has since reneged multiple times on promises to organise elections and hand power back to civilians. Goïta’s action was copied by Mamady Doumbouya in Guinea in September 2021, when he got rid of the civilian president, Alpha Condé, who had changed the Constitution to secure a third term, clamped down on the opposition and organised flawed elections. Doumbouya has announced that he will run as president in elections he has scheduled for December 2025. Burkina Faso followed the coup route in 2022. Military leader Paul-Henri Damiba deposed democratically elected president Roch Kaboré in January 2022. Damiba himself was overthrown in September of the same year by Ibrahim Traoré, a charismatic leader who believes he has a mission to defend Burkina Faso’s independence from Western imperialism and transform the country’s economy. Traoré has declared that he has no intention of going back to the barracks and has since dissolved the national electoral commission. Niger, the fourth country, experienced a military coup in 2023 when Abdourahamane Tchiani ousted the democratically elected president, Mohamed Bazoum. Despite hard-hitting sanctions and threats of military intervention by the Economic Community of West African States (ECOWAS), Tchiani’s regime refused to budge and has consolidated its power. One-third of West Africa’s governments are now under military rule. Beyond West Africa, coups have occurred in recent years also in Sudan, Chad, Gabon and Madagascar—bringing the number of countries in Africa that are ruled by military men to nine. The resurgence of multiple coups within a short period in the 2020s has given rise to the concept of the ‘coup belt’, which spans countries in Sahelian West and Central Africa. However, the regions that are in the coup belt are very similar to those that experienced the highest number of coups between 1963 and 1989, even though East Africa seems to been on a different trajectory since 1990. Jonathan Powell and Clayton Thyne (2025) have painstakingly documented military coups around the world, covering the period from 1950 to the present. Their data is available on the website ‘Global Instances of Coups: 1950-Present’. Duzor and Williamson (2023) have organised this data in two useful graphics that reveal an interesting pattern of coups in Africa. One graphic illustrates the uneven distribution of coups across the continent. West, Central, North and large parts of East Africa are the key regions that were coup-prone before the democratisation process started in the 1990s. Southern Africa largely avoided the coup virus—instead, it was dominated by single-party dictatorships. Lesotho, which experienced a series of military coups, was an outlier in the region. The second graphic demonstrates that between 1990 and 1999 there were still many military coups (successful and aborted), though less than between 1963 and 1989. They fell dramatically between 2000 and 2018, but have experienced an upward swing since 2019. Why have coups become frequent after the lull in the 2000s and 2010s? The seeming frequency of coups demands dispassionate or cool-headed interrogation, beyond the tired practice of support and condemnation. Military rule is not new in Africa. Between 1960 and 1989—before what political scientists have called ‘the third wave of democratisation’—the dominant forms of governance were military rule and single-party dictatorship. There were fifty-seven successful coups in twenty-seven, or about 50 per cent, of African states between 1963 and 1989. The number rises dramatically to more than 90 per cent if attempted coups are included. In 1990, there were only two multiparty democracies—Botswana and Mauritius, both small countries, with barely more than a million people each at the time. The discipline of political science offers two broad explanations for why soldiers intervene in politics. The first, advanced by S. E. Finer (1962) in The Man on Horseback: The Role of the Military in Politics and Samuel Huntington (1968) in Political Order in Changing Societies, emphasises structural issues relating to institutional quality and political culture. It asserts that as the most powerful and organised force in society the military is likely to behave opportunistically in countries with low levels of institutional development. Huntington argued that this happens because all social groups act unilaterally to advance their interests. Military coups, thus, reflect the politicisation of society as groups compete for dominance. The military, as the group with superior coercive powers, invariably wins in such struggles. The second explanation focuses on internal motives or the defence of the military’s corporate self-interests. The leading scholars, Eric Nordlinger (1976) in Soldiers in Politics: Military Coups and Government and Samuel Decalo (1976) in Coups and Army Rule in Africa: Studies in Military Style, argued that the military intervenes in politics largely to protect its self-interests—such as its budget, benefits, autonomy, personnel issues and resisting attempts to create rival militias or security forces. Decalo asserted that ambitious, self-seeking cliques of soldiers, not high-minded military men, typically orchestrate coups in Africa. The literature provides useful insights in trying to understand the history of coups in Africa. However, as this article will demonstrate, it seems inadequate when trying to analyse the resurgence of coups in the last five years. Let’s start with Nordlinger’s and Decalo’s arguments. Corporate interests of the military and internal factional struggles have always been issues in civil-military relations, irrespective of the time period. The questions then become: Why didn’t military grievances push ambitious soldiers to constantly intervene in politics? Were grievances resolved in one period and ignored in another? And is it the case that the military lacked ambitious soldiers to pursue grievances when democratisation was in ascendancy? A similar problem is encountered in Finer’s and Huntington’s arguments. By definition, the link in their argument between low political culture or institutionalisation and military coups is sound—coups, surely, occur only in countries where political institutions are not well developed or where they have crumbled. Their additional argument that the military is a powerful interest group that will intervene when it senses an opportunity is also valid, even though it seems open-ended. However, both arguments do not explain the emergence of what seems like two distinct cycles of military coups in Africa—the long cycle of 1963–1999, and the emerging cycle post 2020. Why were coups less frequent during the period of unipolarity and liberal internationalism (1990 to 2018–2020), but have made a strong resurgence in the current multipolar world? I argue in this article that three developments have made military coups attractive and emboldened soldiers to re-enter the arena of governance. The first is the collapse of the global order of unipolarity and liberal internationalism, which acted as a check on military coups. We call this the external structure of incentives that made military rule untenable. The second is the failure, in most countries, of electoral democracy to live up to its basic principles of free and fair elections, respect for constitutional rule and protection of civic and political rights. And the third is the poor record of democracy to deliver meaningful development and improve citizens’ lives and livelihoods. The first development removes the fear of external sanctions in the calculations of soldiers. And the second and third discredit electoral democracy as a tool for addressing public welfare—they both remove the protection that democracy offers civilian governments to ward off extra-constitutional attacks on civil authority. Global geopolitics and the changing structure of incentives Two developments aided the emergence of democracy as a global force in the 1990s: the collapse of communism in Eastern Europe, and the rejection of one-party and military dictatorships in Africa, Latin America and parts of Asia as systems for promoting economic development and improving citizens’ welfare and security. Both developments signalled the birth of a new era of open global markets, democracy and unipolarity, in which the US was the sole superpower. A remarkable wave of democratisation accompanied these developments. Before 1990, Freedom House, a platform that tracks the global growth of democracy, classified only sixty-six countries as electoral democracies. However, by 2001, the list had increased to 121, or 63 per cent of countries (Freedom House 2002). The Africa story defied belief, given the scepticism in political science scholarship that ruled out the viability of democracy in poor countries. Military and one-party dictatorships crumbled or were forced to organise elections, albeit of varying quality. Independent newspapers bloomed and many countries set time limits on elected leaders. Recognising their dominance in the geopolitical sphere, Western countries embraced the new wave and tried to reorganise the world in a democratic direction. The concept of liberal internationalism, which extols multilateralism, human rights, international law and democracy, gained ground—displacing the notion of realpolitik or pursuit of national self-interests devoid of moral values. In a paper titled ‘The End of the Western Democracy Project in Africa’ (Bangura 2024), I analysed four policy instruments used by Western governments to advance the frontiers of democracy in Africa. These are: support for non-governmental organisations as agents of democratic change; funding and monitoring of elections to ensure credible outcomes; aid allocations for governance reforms to improve state effectiveness; and use of political conditionality to prevent governments from undermining democratic processes. Political conditionality was the centrepiece of the democracy project. Unlike economic conditionalities that had to be met before funds were released under structural adjustment programmes, political conditionality was applied ex-post—aid would be withdrawn or suspended if donors were dissatisfied with the political behaviour of a country. The assumption was that governments would be deterred from disrupting the democratic process if they knew aid would be lost or suspended. However, donors demonstrated a high level of selectivity in applying political conditionality—turning a blind eye to favoured allies or when strategic and economic interests were vital, and punishing those that challenged their interests (Fisher 2014). It is not surprising that an OECD (2022) study found that a striking 79 per cent of all aid was allocated in 2019 to countries classified as autocracies, and only 21 per cent went to democracies. Still, in the context of unipolarity, in which there were no credible alternatives to what Western countries offered in the global economic and political fields, political conditionality changed the structure of incentives that shaped behaviour in Africa. Actors calculated that defying Western pressure would affect aid flows and private investments and even provoke military intervention. They had to adopt strategies that would accommodate elections as a key factor in governance, even when they were not convinced of their merits. Military coups dropped from sixteen in the 1990s to only eight in the 2000s. Significantly, the coups that occurred between 1990 and 2018 were quickly followed by multiparty elections or promises to organise them, even though they did not necessarily produce high levels of democracy. ‘Coup’ became a dirty word in African politics and soldiers knew they would not get away with overthrowing elected governments without organising elections. The rise of China as an economic and technological superpower, Russia’s renewed confidence at the global level and willingness to provide military support to beleaguered leaders in poor countries, and the emergence of new geopolitical blocs that seek to rewrite the old rules of Western hegemony in the global economy in favour of the global South have fundamentally changed the global structure of incentives. For context, with trade valued at USD 200 billion in 2019, China has become Africa’s largest trading partner (Stein and Uddhammar 2023). By 2014, China’s foreign aid—valued at USD 350 billion—had almost levelled up with the US’s USD 394 billion. Of that aid, 45 per cent went to Africa. China is the second-largest source of foreign direct investment and the leading financier of infrastructure projects in Africa—building roads, ports, railways and power plants in many countries. While China offers alternative finance, Russia provides military support to leaders who seek to counter Western military pressures. Through its Africa Corp and other channels, Russia has provided military support to countries as diverse as Mali, Burkina Faso, Niger, Central Africa Republic, Sudan, Libya and Mozambique—often in exchange for mineral resources. This change in the global structure of incentives suggests that rogue leaders—military and civilian—now have options in navigating the trade, investment and aid fields without worrying about political conditionality, and can turn to Russia for protection in the security field. The coup in Niger in 2023 and the failure of ECOWAS (backed by France, the EU and the US) to force the coup leaders to hand power back to the elected leader, despite strong threats of military intervention and wide-ranging sanctions, spelled the death knell of political conditionality in West Africa (Bangura 2024). Western donors and their regional allies (ECOWAS and the African Union, both of which established protocols against unconstitutional changes of government) have been unable to impose their will on renegade soldiers. Indeed, soldiers who topple governments, such as those in Burkina Faso, Mali, Niger and Guinea, are no longer afraid to dismiss democracy as unworkable and try to rule indefinitely. Guinean leader, Doumbouya, even made a scathing denunciation of democracy in a speech at the UN General Assembly in 2023. Democratic regression If political conditionality has lost its deterrence value, large scale democratic regression has dented the assumed virtues of democracy and provided opportunities to ambitious soldiers to seize power. While political scientists are divided on the question of whether there has been a global democratic backsliding or regression (Arriola, Rakner and Van de Walle 2023; Little and Meng 2024; Levitsky and Way, 2023), the evidence of regression in West Africa is incontrovertible. To tackle this issue, it is important first to examine, in comparative perspective, West Africa’s record of democratisation before the decline. As I showed in ‘The End of the Western Democracy Project in Africa’ paper, West Africa experienced more extensive forms of democratisation than other African regions in the 1990s and 2000s. Virtually all West African countries introduced presidential term limits, and incumbent parties were defeated twenty-six times in twelve (75 per cent) out of fifteen countries. For the remaining thirty-nine African countries (excluding Mauritius, where power alternation between parties was common even before the 1990s), incumbent parties lost elections only fifteen times in five countries—Zambia, Malawi, São Tomé, Lesotho and Seychelles. Democratic Botswana joined this group in 2024. As we have observed, five West African countries (Mali, Burkina Faso, Niger, Guinea and Guinea Bissau) are currently ruled by military regimes; two (Togo and Côte d’Ivoire) have extended term limits or lifted them unconstitutionally; and three (Nigeria, Sierra Leone and Benin) have engaged in fraudulent or restrictive electoral practices. Only five countries (Cape Verde, Ghana, Senegal, Liberia and Gambia) can be classified as electoral democracies. Interestingly, eight of the ten countries that have experienced regression held, at least on one occasion, elections in which incumbent parties were defeated. West Africa’s democratic regression is unquestionably profound. Implicated in this regression is the antidemocratic behaviour of leaders who came to office through the ballot box. At least three civilian presidents (Alassane Ouattara, Alpha Condé and Faure Gnassingbé) removed term limits stipulated in their constitutions to enable them rule indefinitely. And even though there are a few bright spots (in Cape Verde, Ghana, Liberia and Senegal), many elections are now routinely rigged in favour of incumbents. Incumbent civilian leaders also increasingly resort to what democracy scholars have described as lawfare, using the courts to ban opposition candidates, remove checks on how they govern and skew electoral contests in their favour. ECOWAS’s record in dealing with electoral malpractices, lawfare and extensions of presidential term limits has been extremely poor, especially in the last seven years. It failed to stop Alpha Condé in Guinea and Alassane Ouattara in Côte d’Ivoire from running for elections for a third term in 2020. It also failed to prevent Ouattara from running for another term in 2025 and using the courts to ban credible opposition figures like Tidjane Thiam from contesting the election. It was largely a bystander in the standoff between Senegal’s then president, Macky Sall, and opposition forces, over Sall’s repression of leading opposition figures, such as Ousmane Sonko and Bassirou Diomaye Faye, and his attempt to extend his stay in office in 2024. ECOWAS also issued muddled interim reports on Nigeria’s and Sierra Leone’s 2023 elections, which most election observers certified as highly flawed. The conclusion is unmistakeable: ECOWAS is more interested in preventing military coups than in holding to account civilian leaders who abuse democratic rules and procedures. Such behaviour has gravely undermined the institution’s authority to defend democracy when soldiers seize power. And voters increasingly find it difficult to differentiate electoral democracy from military rule. Afrobarometer (2023), which tracks political attitudes, found that 53 per cent of those polled in 2021–2022 in thirty-nine countries would consider supporting military rule if elected leaders abused their powers—with 56 per cent of young adults (18–35 years) considering that option. Poor outcomes in development and redistribution The third factor that has emboldened soldiers to seize power is the poor record of electoral democracy in delivering development and improving voters’ welfare, even though economic, social and security conditions hardly improve when the military rules. The literature on the link between democracy and development indicates that regime type is not a predictor of economic growth or development—economies may grow or falter under both democratic and authoritarian regimes. Good outcomes are largely determined by effective institutions and policies, the quality of governmental responsiveness to public demands, and political commitment. Despite more than sixty years of independence and about three decades of electoral democracy, most African economies have yet to achieve far-reaching structural change. Indeed, excluding South Africa, sub-Saharan Africa is the only region in the world that has not experienced substantial industrialisation. The notion of redistribution that underpinned democracy’s early history seems also to be absent in much of Africa’s democracies. This has implications for the consolidation and survival of democracies. The share of manufacturing in Africa’s GDP stagnated at about 10 per cent for much of the 2000s, and employment at about 14 per cent, and neither improved meaningfully in subsequent years. Traditional agriculture and the low end of the informal sector still employ most people. Structural change has largely involved a movement from agriculture to mining, which employs fewer people. Poor economic growth is a big reason for the poor performance—its level and quality has not been high and consistent enough to transform societies. Impressive GDP growth rates ranging from 7 to 10 per cent have been recorded in recent years in some countries, such as Côte d’Ivoire, Benin, Niger, Guinea and Senegal. However, even in these countries, high growth rates have not led to structural change and marked improvements in living standards. Of the twenty-five countries classified as having low human development in the 2024 Human Development Index—an aggregate index of per capita income, life expectancy and literacy—eleven are in West Africa. High-growth countries—Côte d’Ivoire, Benin, Niger, Guinea and Senegal—are among the poor performers. Africa’s GDP per capita, a crude but widely used measure of the average income of citizens on the continent, almost tripled from a low of about USD 629 in 2000 to about USD 1,880 in 2014 (Macrotrends n.d.). This was the period of the so-called ‘super commodity cycle’—when commodity prices seemed to be experiencing a long-term boom and the Afropessimism of the 1980s and 1990s was giving way to a narrative of Africa Rising. However, by 2016, per capita income had fallen sharply to USD 1,447, dashing hopes of an emerging transformation. Even though by 2023 per capita income recovered to USD 1,623, it still is barely above the income level of USD 1,145 used by the World Bank to characterise the poorest, or low-income, countries in the world. Poverty figures are also dire. The World Bank estimates that 62 per cent of people in extreme poverty live in Africa, with an average poverty rate of 37 per cent.. Even though extreme poverty is lower in West Africa (36.8 per cent) than in Central (54.8 per cent) and southern Africa (45.1 per cent), the region’s 36.8 per cent extreme poverty rate is a stress factor that affects political choices and security. Unemployed and poor young men are being pulled into banditry and violent jihadist activities—as Nigeria, Niger, Burkina Faso and Mali have experienced in recent times. Africa’s inequality (its Gini index is 0.43) is also higher than the global average, with many countries in southern Africa having levels of inequality that are among the highest in the world. However, social protection programmes that try to address inequalities seem more advanced in southern Africa than in West Africa. Oxfam’s ‘Committed to Reducing Inequality Index’, which measures programmes in education, health, social protection, taxation and workers’ rights, revealed in 2022 that West African governments were the least committed to reducing inequality in Africa. It found that fourteen out of sixteen countries in the region signalled that they would cut their budgets by a ‘combined USD 26.8 billion’ over a five-year period after the Covid pandemic of 2020–2022. Citizens’ confidence in democracy may falter when it fails to address voters’ lives and livelihoods. The situation may become untenable when poor socioeconomic performance combines with the failure of electoral democracies to offer credible pathways for mandate renewal. Africa’s democracies need a major rethink Let me conclude. The electoral politics that have emerged in much of Africa since 1990 substantially lack democracy’s basic qualities of free and fair elections, civil and political rights and redistributive policies—features that historically endeared democracy to working people or citizens. Unless these issues are addressed, Africa’s truncated democracies will always face authoritarian challenges from the military and other forces. Democracy requires that those who govern do so through the mandates of citizens in free and fair elections, and that a body of rights—on expression, assembly, organisation and protest—exists that enables citizens to make informed choices and hold office-holders accountable. Rational choice theory has provided valuable insights on the limitations of representative democracy in advancing the complex interests of citizens in public policy. These insights may have relevance for understanding democratic backsliding and the disconnect that has been observed between politicians and citizens in the field of economic and social development. Since direct democracy (in which citizens meet regularly and take collective decisions) is impossible in modern societies, a least-worst system—representative democracy—was crafted, in which citizens elect representatives to act on their behalf. However, representative democracy is bedevilled with a principle–agent problem: agents, or representatives, may be captured by powerful interests, or agents may decide to pursue their own self-interests. Efforts to minimise the principle–agent problem may explain why broad social forces were key drivers in transitions from despotic rule to representative democracy in countries that first embraced this system of government. Lipset and Rokan (1967) observed that in Western industrial democracies, social movements, civic associations and political parties tended to cluster based on the classic division between capital and labour associated with industrialisation. Many political parties were a product of social movements and associations. Indeed, parties were formed to contest elections and pursue the interests of movement members or supporters. Leaders, acting as agents, had limited leeway to pursue personal agendas. In some countries, social movements inserted themselves in the policymaking arena, through collective bargaining and social pacts, to defend core interests (such as wages, employment and social protection) and prevent rogue behaviour by politicians or agent defection. Democracy may seem like a benign system of government today. However, ruling or propertied classes were initially afraid of it, since it meant ‘rule of the people, by the people and for the people’—to use Abraham Lincoln’s simple but effective definition; and working people equated democracy with socioeconomic redistribution that improves mass living standards. John Stephens (2007) has shown that democracy and welfare development in advanced industrial societies were driven by the same social forces and processes. People voted because they wanted welfare protection and expansion. Working-class voting in the early period of European democratisation correlated strongly with the expansion of welfare programmes in critical areas such as work accidents, health, pensions and unemployment. Social spending, social programmes and taxation increased, and inequalities declined after countries embarked on democratisation (Acemoglu and Robinson 1999; Boix 2003). Africa’s democratisation is different. Even though a large number of social movements drove the democratic transitions in Africa in the 1990s, most of the parties that emerged lacked strong structural ties to social interests or movements (Bangura 2015). The new parties not only enjoyed enormous freedom to do as they wished, the power elite who controlled them also enjoyed arbitrary powers to dictate policy with little or no accountability to members. Democracy, therefore, lost its ability to sanction poor performance or incentivise politicians to pursue policies that improve the wellbeing of voters. The key issue democracy advocates need to confront is not whether the military is a poor alternative to democracy. Military rule is, surely, inferior if we compare it to the type of democracy outlined above. Military rule has a poor record of repression, atrocities, corruption, incompetence and mismanagement. There is a good reason citizens massively rejected it in the 1990s. However, harping on its historical recklessness will not be enough to convince the majority of young people who have never experienced army rule and crave alternatives to civilian systems of rule they believe are not working. The survival of Africa’s democracies requires changes in the way parties are formed and choices made in public policy. It calls for the rejection of practices that have truncated the virtues of democracy and for taking redistributive issues seriously. Opportunistic military leaders who are no longer constrained by external political conditionality may strike if they believe voters are unhappy with the quality of democracy that governs their lives.